2021
DOI: 10.3390/en14237866
|View full text |Cite
|
Sign up to set email alerts
|

Modeling the TetraSpar Floating Offshore Wind Turbine Foundation as a Flexible Structure in OrcaFlex and OpenFAST

Abstract: Floating offshore wind turbine technology has seen an increasing and continuous development in recent years. When designing the floating platforms, both experimental and numerical tools are applied, with the latter often using time-domain solvers based on hydro-load estimation from a Morison approach or a boundary element method. Commercial software packages such as OrcaFlex, or open-source software such as OpenFAST, are often used where the floater is modeled as a rigid six degree-of-freedom body with loads a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…Motions and loads predicted by the open-source OpenFAST and commercial OrcaFlex codes for an FWTS are compared together by [293] and it is shown that the predictions provided by these codes are generally in good agreement.…”
Section: Recent Researchmentioning
confidence: 99%
“…Motions and loads predicted by the open-source OpenFAST and commercial OrcaFlex codes for an FWTS are compared together by [293] and it is shown that the predictions provided by these codes are generally in good agreement.…”
Section: Recent Researchmentioning
confidence: 99%
“…The Simo/Riflex code was verified against some software of the Offshore Code Comparison project such as FAST, Adams and HAWC2 in Luxcey et al (2011); Ormberg et al (2011) while five numerical models that included some variations of a Simo/Riflex/Aerodyn were compared in Luan et al (2017). Motion and loads of the TetraSpar floating platform were compared between OpenFast and OrcaFlex, with a generally good agreement, including the flexibility of the structure (Thomsen et al 2021). The various studies discussed here have generally shown reasonable agreement bewteen numerical models and experimental studies.…”
Section: Numerical Model Validation and Verificationmentioning
confidence: 99%
“…The Institute for Energy Technology in Norway describes in [11] an FEM-approach in their 3DFloat software to model flexible substructures, but 3DFloat is also relatively slow (several times slower than real-time), but it can be parallelized. In [12], flexible substructures of FOWT are simulated both with OpenFAST and OrcaFlex and the results are compared to rigid equivalents. A hydrodynamic potential flow assumption was implemented in a time-domain analysis using modal decomposition in [13].…”
Section: State Of the Artmentioning
confidence: 99%